(untitled) (Technical Journal, 2019)
Hybridization is always done in search of better system which may not be always achieved. But most of the time hybridization has proved to produce a system with advantages of the algorithms used in developing that hybrid system. Even if the system doesn’t have performance enhancement it will act as multi-layer security. Here, combing of Blowfish algorithm along with ECC algorithm is performed. After hybridization their performance analysis is done based on five different parameters with different key size of Blowfish algorithm i.e. 32 bit, 128 bit, 192 bit, 256 bit, 448 bit. Among these different hybrid cryptosystem we found that the Blowfish ECC system with key size 448 bit has better performance than all other bit size.